Tracing the origin of intravenous infusion technology in China (国内静脉输液技术溯源) - E Haiyan (鄂海燕); Wang Yali (王亚丽); TANG Ling (唐玲); WEI Yongchun (魏永春); JIANG Jing (姜婧); DONG Yuxia (董玉霞) (Journal of International Translational Medicine Limited, 2022)
With the progress of medicine, great changes have taken place in intravenous infusion technology. This paper summarizes the development process of intravenous therapy in China from the aspects of the origin of intravenous infusion technology, the innovation of static therapy tools, the construction of professional team, norms and standards, in order to improve the safety, scientificity and effectiveness of intravenous infusion and maintain the life channel of patients. (随着医学的进步, 静脉输液技术也发生了很大的变化。本文从静脉输液技术起源、静疗工具革新、专业化队伍建设、规范与标准等方面对国内静脉治疗的发展进行综述, 旨在提高静脉输液的安全性、科学性、有效性, 维护患者的生命通道。)